Hungarian feminist geography in a curved space? - Timár, Judit (Gender, Place & Culture: A Journal of Feminist Geography)
The history of feminist geography in Hungary coincides with the 25 year-long history of Gender, Place and Culture. Authorities denied the existence of gender inequality in the era of state socialism, which was the primary obstacle to the spread of gender studies. The political changes that had occurred after 1989 had removed most obstacles, but feminist geography emerged with a delay relative to other disciplines. Its first two decades was characterised by struggles and compromises within and against the geographical discipline in order for it to win recognition. The 25 year-long history of feminist studies has, however, been completely broken by legislation proposed by the current government suggesting a ban on masters programs in gender studies. In this article, I trace the situation of feminist geography in Hungary by applying the concept ʻcurved spaceʼ. This concept adapted from modern physics claims that mass creates a gravitational field, i.e. it bends 4-dimensional ʻspacetimeʼ. My argument is that the situation of feminist geography in Hungary can be interpreted as an embodiment of ʻcurved spaceʼ. Using this analogy, I argue that the current Hungarian government has amassed such a huge amount of power that has enabled it to curve the space of feminist geographical knowledge production. It has established a quasi-dictatorship that resembles the one that impeded the evolution of gender/feminist geography in the state socialist era. Therefore, only broad-based solidarity can help create opposition to the current government's attacks against gender studies.